Formation of Multicultural Competence of the Teacher of Native (Tatar) Language in the Context of Advanced Training Program Implementation - Rezida N. Safina (Publishing house "Sreda", 2020)
The ways and means of implementing the contents of an additional professional educational advanced training program consisting of classroom and extracurricular activities aimed at incorporating the mastered experience into the practice of trainees (listeners) to solve specific problems of professional activity are considered. Based on the analysis of legal documents and scientific and methodical literature, the purpose, objectives and content of the formation of professional competences of teachers of the native (Tatar) language within the additional advanced training program implementation and post-course period have been determined. The purpose of the study is to reveal the possibilities of additional professional educational advanced training program aimed at improving the multicultural competence of the teacher of native (Tatar) language "Formation of multicultural competences of the teacher of teacher of native (Tatar) language". The author outlines that the aim of the additional professional educational program is to improve the professional competence of teachers of the native (Tatar) language, oriented and ready to work in a multicultural educational environment at the entry stage of Russian school in international competition. Methods. During the implementation of the program the following methods were applied: reflexive analysis, modeling, case-study, project method, etc. It is concluded that professional competences formed during the implementation of the additional professional educational advanced training program are designed to implement the tasks of multicultural education in practical activities of teachers of the native (Tatar) language.